Mechanochromic luminescent materials with aggregation-induced emission: Mechanism study and application for pressure measuring and mechanical printing. (February 2020) - Shi, Peijun; Deng, Dan; He, Chuhuan; Ji, Lin; Duan, Yuai; Han, Tianyu; Suo, Bingbing; Zou, Wenli
Abstract: In this work, we report the synthesis and emission behavior of two analogue compounds, 2-(( E )-((9H-fluoren-2-yl)methylene)amino)-3-aminomaleonitrile (C1 ) and 2-amino-3-(( E )-(4-(diphenylamino)benzylidene)amino)maleonitrile (C2 ). The two compounds exert both aggregation-induced emission (AIE) nature and intramolecular charge transfer (ICT) character. They show mechanochromic luminescence (MCL) in different ways: The C1 solid powder has strong green emission but would be quenched without color change after grinding. While C2 shows strong green emission in powder form but turns orange-red with a 30% loss in the quantum efficiency after grinding. The force-induced emission of both C1 and C2 can be changed back to the starting state by a simple immersion treatment in organic solvents, suggesting high fatigue resistance. Their MCL mechanisms were studied base on spectroscopic analysis combined with quantum chemical calculation. Powder x-ray diffraction (PXRD) diffractograms suggest a decrease in crystallinity rather than a full amorphization, excluding the phase transition mechanism that has been widely accepted for most of the MCL materials in prior reports. The photophysical process has been modeled according to the quantum chemical calculation using DFT-PBE0/6-311g (d, p), two stable isomers of C1 were detected, which exhibit structural relaxation with a conical intersection seam. The conical intersection of C1 can be accessed by mechanical stimuli but is unable to reach in the starting crystalline phase due to conformation rigidity. In contrast, such structural relaxation is less possible with C2 due to high emission in solution state. And the MCL mechanism mainly involves conformation planarizartion, which leads to bathochromic-shift with its emission. The new working mechanism with C1 is superior to other counterparts on account of its sensitivity and practicability. A new type of pressure sensor based on C1 film was developed, showing remarkable quenching effect with the pressure. A linear relation between pressure and emission intensity was obtained, offering a low detection limit down to 22.92 Mpa. This mechanochromic system succeeds in mechanical printing using MCL: Pressure up to 30 Mpa clearly imprints the cartoon patterns in detail with high contrast using the MCL materials, demonstrating a feasible prototype of printing technology. Graphical abstract: Image 1 Highlights: Structural relaxation with a conical intersection seam is used to explain mechanochromic luminescence. A film sensor for pressure measuring is developed, showing high sensitivity. This mechanochromic system succeeds in mechanical printing.